2021
DOI: 10.1002/oby.23195
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as an isolated contraindication to kidney transplantation in the end‐stage renal disease population: A cohort study

Abstract: There are approximately 125,000 newly reported cases of end-stage renal disease (ESRD) annually in the United States, with nearly 750,000 prevalent cases (1). However, only 13.7% are actively listed for kidney transplantation, despite improvements in survival, quality of life, and economic savings compared with dialysis (1-7). Listing for transplant requires a thorough psychosocial and medical assessment-including evaluation for obesity-that precludes many from pursuing transplant.The rising obesity epidemic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…2 Importantly, not all eligible patients have the same chance of receiving a life-saving transplant. For example, a large body of literature now indicates that patients of lower (vs. higher) socioeconomic status, 3 , 4 , 5 Black (vs. White) patients, 6 , 7 , 8 , 9 and obese (vs. nonobese) patients 10 , 11 are less likely to receive a transplant.…”
mentioning
confidence: 99%
“…2 Importantly, not all eligible patients have the same chance of receiving a life-saving transplant. For example, a large body of literature now indicates that patients of lower (vs. higher) socioeconomic status, 3 , 4 , 5 Black (vs. White) patients, 6 , 7 , 8 , 9 and obese (vs. nonobese) patients 10 , 11 are less likely to receive a transplant.…”
mentioning
confidence: 99%
“…If they do make it onto the transplant list, their weight may still keep them from receiving a kidney transplant. 12 For this group of patients, weight loss must be achieved, and bariatric surgery before kidney transplant may be a possible way to ensure that eligible patients get their much-needed kidney transplant. 5 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…A higher BMI has been associated with a lower likelihood of listing, and of those with BMI 35-39.9 kg/m 2 who were already listed, 24% were less likely to actually achieve transplant. 12 Previous studies have recommended bariatric surgery to obtain sufficient weight loss in patients with kidney failure, 5 , 13 , 14 and other studies have suggested that patients treated with dialysis with obesity need intensive weight-loss counseling to prepare for a kidney transplant. 15 Studies have shown that these patients are well aware of their obesity and the need to lose weight but feel unable to do so.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to delay or prevent ESKD progression through weight loss with antiobesity medications presents an opportunity to prevent dialysis's morbidity and mortality for patients with obesity. For patients with advanced CKD or ESKD, weight loss with pharmacotherapy may overcome welldocumented disparities in access to kidney transplantation, the preferred ESKD treatment [19][20][21]; however, there are limitations to the use of most of these medications for patients suffering from both obesity and diminished kidney function.…”
Section: Introductionmentioning
confidence: 99%